Looking Back, Looking Forward: Reflections and Hopes for Inclusive Comparative and International Education: CIESC Presidential Address, May 31, 2021 - Sider, Steve (Comparative and International Education / Éducation comparée et internationale, 2022)
In my 2021 CIESC presidential address, I considered the question “What can inclusive comparative and international education research look like?” I situated my own experience to consider three “Cs” for the future of comparative and international education: complexity, care, and cautions. Complexity refers to the divisive and challenging global issues that exist and in which comparative education research takes place. As comparative and international education researchers, we need to practise an ethic of care in engaging in research in increasingly complex times. I concluded by providing three cautions for the future of research: transparency, positionality, and ethical relationality.